ESTIMASI GEOLOGICAL STRENGTH INDEX (GSI) SYSTEM PADA LAPISAN BATUGAMPING BERONGGA DI TAMBANG KUARI BLOK SAWIR TUBAN JAWA TIMUR - Erwin Wijaya, R. Andy; Karnawati, Dwikorita; ., Srijono; Wilopo, Wahyu; Isnawan, Dianto (PROMINE, 2014)
The limestone mine activity needs a good mine plan design with the result that saved for the environment. Mine design is determined by rock mass quality. The rock mass quality in each mine location is different and that is influenced by the geological conditions. Research area is located in limestone quarry Sawir Block of Kerek District, Tuban Regency, East Java Province. In limestone quarry area, there is cavity zone which consists cavity limestone layer at the wall of quarry bench. This cavity layer in limestone quarry has occurred by solution process. The cavity layer zone has more potential as weak zone which caused failure of bench in limestone quarry area. To analyze of the research of rock mass quality in cavity limestone layer using Geological Strength Index (GSI) system. Final result of the research is rock mass characterization specifically for cavity limestone layer. Keywords: Geological strength index, limestone, cavity layer